2010
DOI: 10.1021/jm901523t
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Screening Hit Reveals New Possibilities for Developing Group III Metabotropic Glutamate Receptor Agonists

Abstract: (R)-PCEP (3-amino-3-carboxypropyl-2'-carboxyethyl phosphinic acid, 1), a new metabotropic glutamate receptor 4 (mGlu4R) agonist, was discovered in a previously reported virtual screening. The (S)-enantiomer and a series of derivatives were synthesized and tested on recombinant mGlu4 receptors. A large number of derivatives activated this receptor but was not able to discriminate between mGlu4 and mGlu8 receptors. The most potent ones 6 and 12 displayed an EC(50) of 1.0 +/- 0.2 microM at mGlu4R. Interestingly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 44 publications
(159 reference statements)
2
65
0
Order By: Relevance
“…Mutagenesis data confirmed that cinnabarinic acid binds to the orthosteric site of mGlu4 receptor. Cinnabarinic acid was thus docked in the mGlu4 receptor closed extracellular domain homology model that we described previously (Selvam et al, 2010). The molecule fits nicely in the cleft between the two lobes close to the hinge (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Mutagenesis data confirmed that cinnabarinic acid binds to the orthosteric site of mGlu4 receptor. Cinnabarinic acid was thus docked in the mGlu4 receptor closed extracellular domain homology model that we described previously (Selvam et al, 2010). The molecule fits nicely in the cleft between the two lobes close to the hinge (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Cinnabarinic acid was docked in a homology model of mGlu4R amino terminal domain previously validated (Selvam et al, 2010). The ligand was initially positioned in the binding site using GOLD version 4.1 (http://www.ccdc.cam.ac.uk/ products/life_sciences/gold/).…”
Section: Molecular Modeling: Docking Of Cinnabarinic Acid In Mglu4 Ammentioning
confidence: 99%
“…These small molecules are new allosteric modulators and are called extracellular domain allosteric modulators (EDAM). To date, there are three groups of EDAMs and their corresponding sites have been identified: IMP to the T1R1 VFT of the umami taste receptor [31] , SE-2/SE-3 to the T1R2 VFT of the sweet taste receptor [67] and the (R)-PCEP derivatives with long alkyl chains to the VFT of the mGlu4 receptor [68,69] .…”
Section: Tm Allosteric Sitesmentioning
confidence: 99%
“…At mGlu receptors, the glutamate-binding pocket is well conserved across the mGlu subtypes, encumbering the discovery selective orthosteric agonists and antagonists (Brauner-Osborne et al, 2007). However, recently, long alkyl chain containing derivatives of (R)-PCEP, a molecule discovered by virtual screening on the VFT of mGlu receptors, revealed a new binding pocket in mGlu 4 (Selvam et al, 2010). Indeed, these compounds not only bind in the glutamate-binding pocket itself, but may also interact with a novel, putative binding pocket adjacent to the glutamate-binding site.…”
Section: Group III Mglu Receptors and Their Ligandsmentioning
confidence: 99%